Risk to pollution of aquifers associated with productive activities and environmental management of water resources: bibliometric analysis and trends - Yepes, Gloria Yaneth Florez; Álvarez, Angela María Alzate; Cardona, Paola Vásquez; Marín, Luis Alberto Vargas; Arcila, Erika Juliana Aldana; Hoyos, Fredy E. (Institute of Advanced Engineering and Science, 2024)
Its analyzed the evolution and trends of the concept, and studies the models used to know the vulnerability and risk of aquifers and strategies for their management. The methodological process starts from questions guiding the knowledge of research trends, authors among others to proceed to carry out the analyses from the databases of Scopus, Web of Science and Dimensions. VOSviewer and Bibliometric (Rstudio) software were used. Among the most representative results, it was found that most of the research to determine the risk of aquifer contamination is focused on different models such as improved flux prototypes for NO2 emission from agriculture (IPNOA), pollutant origin surcharge hydraulically (POSH), intrinsic vulnerability methods ground water occurrence, overall aquifer class, depth to groundwater (GOD), depth recharge, aquifer, soil, topography, impact, hydraulic conductivity (DRASTIC), substance, infiltration, not saturated, type of coverage, topographic surface, conductivity (SINTACS) and chlorofluorocarbons (CFC) among others. Different models have been used that integrate both hydrological and hydro-geological aspects as well as social aspects including fundamental rights, other models such as the diffuse model, which has had better results in its application, the gaps in the research, are especially focused on conducting holistic research when assessing the risk of these dynamical systems.